Social Status and the Effects of Legal Concealed Firearms on College Campuses. Issue 3 (3rd July 2019) - Soboroff, Shane; Lovekamp, William; Jenkot, Robert
Abstract: Research consistently shows that students and faculty are generally against expanding access to firearms on campus, and many stakeholders worry about the effects of campus carry laws on student violence, civility, and feelings of safety. We contribute to this literature by investigating how potential changes to campus carry policies affect students' reported commitment to campus activities. Theories explaining fear of crime and social commitment led to hypotheses that predict members of socially disadvantaged groups—specifically women and minority students—would report less favorable attitudes toward gun possession on campus, greater feelings of vulnerability to victimization, and less commitment to the college environment when students or staff may possess guns. Hypotheses received support, and add to the growing literature documenting potential issues that legislators, administrators, and faculty might consider when debating the enactment of campus carry policies.